Valley-optical properties in layered 2D transition metal dichalcogenides - Huang, Zumeng (Nanyang Technological University, 2021)
Two-dimensional Transition Metal Dichalcogenides (TMDs) are a group of materials that draws intensive research interests because of their unique valley contrasting physics, in the application of next generation spintronics and valleytronics. Recently, the stacking of 2D TMDs to form heterostructures of layered TMDs have shown enhanced spin-valley phenomenon including longer exciton lifetime and valley lifetime. They also feature strong electron-electron correlation in the vicinity of Mott transition density for heterostructures with a moiré potential. All these properties provide opportunities for deeper understanding of TMDs valley physics. Here in this thesis, three aspects of the valley-optical physics in layered TMDs heterostructures is presented.